2019
DOI: 10.1051/matecconf/201927302008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of STPA and Bow-tie Method Outcomes in the Development and Testing of an Automated Water Quality Management System

Abstract: The technology available to water quality management applications needs to be advanced due to greater use of automation to increase ease of operation, support remote operation and reduce risks due to operator error. In this case study, a comparison is made between System-Theoretic Process Analysis (STPA) and the Bow-tie methodology for identifying process hazards and countermeasures which can be used to guide the design and testing of an automated water quality management system (AWQMS). For this study, the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Following the identification CF for the UCAs, to provide information on how to reduce risk associated with UCAs the next step is to identify suitable countermeasures for each CF. The countermeasures are actions required to either prevent the causal scenario from occurring or reduce the impacts of the relevant CF for the scenarios considered [34]. It's these countermeasures which are included in the program requirements to reduce the risk of unsafe or out of spec water being produced by the catchment.…”
Section: Stpa Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Following the identification CF for the UCAs, to provide information on how to reduce risk associated with UCAs the next step is to identify suitable countermeasures for each CF. The countermeasures are actions required to either prevent the causal scenario from occurring or reduce the impacts of the relevant CF for the scenarios considered [34]. It's these countermeasures which are included in the program requirements to reduce the risk of unsafe or out of spec water being produced by the catchment.…”
Section: Stpa Methodologymentioning
confidence: 99%
“…For the formal STPA method the identification of causal factors is normally the last step but, in this study, countermeasures were considered for each CF. The process of identifying countermeasures consists of reviewing each causal factor and identifying requirements to either prevent the CFs from occurring or reduce the potential for causal factors to result in a UCA [34]. A review of the CFs showed that more than one viable countermeasure can be applied to many CFs.…”
Section: Loss Scenarios and Countermeasuresmentioning
confidence: 99%
“…Following the CFs identification, and in order to provide information on how to reduce the CF-related risk associated with UCAs, the next step is to identify appropriate "safeguards" for each CF. The safeguards are actions required to either prevent the causal scenario from occurring or reduce the impact on the scenarios perceived by the relevant CF [34].…”
Section: Loss Scenariosmentioning
confidence: 99%
“…For the formal STPA method, the identification of causal factors is normally the last step, but, in this study, countermeasures were considered for each CF. The process of identifying countermeasures consists of reviewing each causal factor and identifying requirements to either prevent the CFs from occurring or reduce the potential for causal factors to result in a UCA [32]. The initial investigation of the CFs showed that more than one viable countermeasure can be applied to many CFs.…”
Section: Loss Scenarios and Countermeasuresmentioning
confidence: 99%
“…Following the identification CF for the UCAs, to provide information on how to reduce risk associated with UCAs, the next step is to identify suitable countermeasures for each CF. The countermeasures are actions required to either prevent the causal scenario from occurring or to reduce the impacts of the relevant CF for the scenarios considered [32]. It is these countermeasures that are included in the program requirements to reduce the risk of unsafe or out of spec water being produced by the catchment.…”
mentioning
confidence: 99%